Key Performance Indicators (KPIs) in the Change Management of Public Administration - Bala, Adisa; Koxhaj, Andrea (European Scientific Journal, ESJ, 2017)
This paper is part of my progress work within the research topic focused on change management process in the public administration. The aim will be describing some specific and crucial milestones of this challenging process. Change is inevitable and a continuous process if we want to improve our public administration. If we refer to change management the first element we cross through is the concept of a new system, regulation, structure ect. While introducing the change, we have to take care not only to the context, to the typology of the process, its factors and actors. The most important is considering the successful results in the mean of facing and applying it. But how can we define this success in the terms of public administration? Which can be some measurements to use in order to evaluate the performance of change management? How is performance management linked to an effective, efficient or a viable change management? I will try to answer to these concerns, through explaining further the general key indicators of determining performance in public administration in order to lead a successful process of managing the change.